Survival Nomogram for Lung Adenocarcinoma Patients With Bone Metastasis Based on the SEER Database and an External Validation Cohort - Zhiming Liu; Min Zhang; Shuo Han; Hao Zhang; Shengwei Meng; Zhubin Shen; Xuexiao Ma (Cancer Reports)
ABSTRACT Background Lung adenocarcinoma is a common type of cancer that can lead to bone metastasis and has a poor prognosis. Although previous studies have established nomograms for lung adenocarcinoma, these nomograms do not effectively predict the prognosis of lung adenocarcinoma patients with bone metastasis. This study aims to establish and validate a new nomogram to solve this problem. Methods Data were collected from the SEER database and from patients at our hospital who had been diagnosed with lung adenocarcinoma and developed bone metastases. The patients were randomly assigned into the training and internal validation sets in a 7:3 ratio. External validation was conducted using an independent patient cohort from two hospitals. Different methods were used to evaluate the nomogram's performance. The relationship between different metastatic sites and radiotherapy and chemotherapy was also analyzed to evaluate patient prognosis. Results The following factors were identified as significant prognostic indicators: age, sex, marital status, T stage, N stage, tumor grade, tumor size, presence of brain and liver metastases, and receipt of chemotherapy. The nomogram's concordance indices for predicting overall survival were consistently above 0.7, and the area under the curve values, calibration plots, and decision curves all confirmed the nomogram's strong predictive accuracy. Moreover, our analysis revealed that chemotherapy was the most effective treatment modality. Conclusions This study developed a nomogram that can predict the prognosis of lung adenocarcinoma patients with bone metastasis. The results showed that patients with liver metastasis had the worst prognosis and that chemotherapy was the most effective treatment regimen for patients with different metastatic sites.